Effect of Leadership Styles on Employee Productivity in JUHEL Pharmaceutical Firm Anambra State Nigeria - Nebolisa Chinwe Mikella; Omene Rita Awele (Educational Dynamics: International Journal of Education and Social Sciences, 2025)
This study investigated the effects of different leadership styles on employee productivity in JUHEL Pharmaceutical Firm, Anambra State, Nigeria. The primary objectives were to analyze the impact of transformational leadership, evaluate transactional leadership, and explore laissez-faire leadership's influence on productivity, as well as compare these styles' overall effectiveness. Using a quantitative approach, data were collected from 66 employees through structured surveys. Descriptive statistics, correlation analysis, and ANOVA were employed for data analysis. The findings revealed that transformational leadership had a significant positive effect on employee productivity, enhancing motivation and performance. Transactional leadership showed a moderate impact, fostering goal-oriented behaviors and structured work environments. Conversely, laissez-faire leadership was found to have a minimal effect on productivity, often leading to lower employee engagement due to insufficient guidance. Comparative analysis indicated that transformational leadership outperformed the other styles in promoting higher productivity metrics. This study highlights the importance of effective leadership strategies for enhancing productivity in pharmaceutical firms. It suggests that JUHEL Pharmaceutical Firm and similar organizations should prioritize transformational leadership development to achieve optimal performance. The research contributes valuable insights to the field of leadership studies and offers a basis for future investigations into leadership practices and productivity outcomes.